2020
DOI: 10.1080/09593985.2020.1731895
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study exploring physical therapists’ views on the Otago Exercise Programme for fall prevention: a stepping stone to “age in place” and to give faith in the future

Abstract: Background: One of the most effective interventions to prevent falls is exercise. A commonly used program that prevents falls is the Otago Exercise Programme (OEP). Despite this, user-based knowledge of its applicability in real-world settings for older adults who are dependent on formal care in their homes is lacking. Purposes: To explore how physical therapists (PTs) experience the applicability of the OEP in clinical practice for home-dwelling older adults who are dependent on formal home care and to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…This result was also verified in the interview survey. According to their many years of practical experience, 17 physiotherapists concluded that OEP can improve older adult's sense of fall efficacy, expand their social participation and promote older adult to better manage their daily life ( 54 ). An intervention study based on technical means believes that both online group exercise and social model OEP can improve the loneliness of older adult to a certain extent and improve the level of subjective wellbeing of older adult ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result was also verified in the interview survey. According to their many years of practical experience, 17 physiotherapists concluded that OEP can improve older adult's sense of fall efficacy, expand their social participation and promote older adult to better manage their daily life ( 54 ). An intervention study based on technical means believes that both online group exercise and social model OEP can improve the loneliness of older adult to a certain extent and improve the level of subjective wellbeing of older adult ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the physiological mechanism of OEP improving lower limb muscle strength is not clear, and whether it will increase bone mineral density and muscle cross-sectional area is unknown, but there is no doubt that it can delay muscle atrophy. From the perspective of the impact of older adult's fall efficiency, it is mainly to improve older adult's fall efficiency, increase their self-confidence, overcome the fear of previous falls, and enable them to complete some self-management things independently, so that they are full of confidence in their later life ( 54 , 60 ), to achieve the purpose of reducing the risk of falls. The long-term sedentary elderly at home can alleviate the mood of depression and loneliness through OEP, expand social participation, enhance the feelings of their families and obtain the support of their families when exercising at home with their families, to improve the subjective wellbeing of older adult, which is very important for older adult who cannot go out of home due to physical factors.…”
Section: Discussionmentioning
confidence: 99%
“…As correlações significantes encontradas entre o desempenho anterior e posterior ao programa de intervenção corroboraram com os resultados de ensaios clínicos de outras pesquisas (4,12,15,25) que concluíram a eficácia dos exercícios de Cawthorne e Cooksey na prevenção de quedas em idosos. A utilização de outros recursos como exercícios multissensoriais, programa de fortalecimento de membros inferiores, tai Chi e dança, também, foram relatados (2,9,(26)(27)(28)(29) como estratégias para melhorar o equilíbrio funcional, a mobilidade e a marcha, sendo assim, bons mecanismos a serem explorados para ações que objetivam um envelhecimento saudável.…”
Section: Discussionunclassified
“…Falls are among the most prevalent and debilitating health issues that hinder older adults’ capability to age in place [ 1 , 2 ]. Older adults living with dementia (OLWD) experience greatly heightened fall risk compared to their age-matched peers without dementia [ 3 ] due to various biological, cognitive, and behavioural risk factors [ 4 ].…”
Section: Introductionmentioning
confidence: 99%